On Caristi Type Maps and Generalized Distances with Applications - Wei-Shih Du (Abstract and Applied Analysis)
We prove some new existence theorems of fixed points for Caristi type maps and some suitable generalized distances without lower semicontinuity assumptions on dominated functions. As applications of our results, some new fixed point theorems and new generalizations of the Banach contraction principle are given.